Process model for two-dimensional braiding of elliptical cross-section preforms. - Eustace, Stephen A. (University of Ottawa (Canada), 1998)
One form of composite material consists of an amorphous matrix (generally a polymer) with a set of fibres contained in fibre bundles or strands, embedded within it. Often the strands are arranged in an interwoven fabric. Two-dimensional (2D) braiding provides one means of creating such a fabric. The composite's properties depend very much on the configuration of the strands. This configuration depends on aspects of the braiding process, such as machine size and machine speeds. Thus there is a need to establish the relationships between the process parameters and the resulting configuration for braiding processes. In this research effort, relationships of this type were developed for hollow tubular fabric "preforms" with an elliptical cross-section that varies in size along the product's length. These relationships take the form of both single line equations and algorithms with several inherent equations and decision steps. The algorithms give the property distributions over the preform surface. Relationships were developed for both steady state and transient processes. The algorithms, which were run for various process and mandrel conditions, gave reasonable results. When run for circular cylindrical preforms, the results agreed with previously published work.
Keywords: Engineering, Mechanical.